DIGITALIZATION OF ISLAMIC EDUCATION PLANNING IN MADRASAH - Agnes Prihastia; Umi Hani; Silmi Mausul; Daimah Daimah; Maskun Safi’i (Perkumpulan Manajer Pendidikan Islam (PERMAPENDIS) Indonesia, 2022)
The entry of Indonesia in the era of the industrial revolution 4.0 caused various changes in various sectors of life in society such as the order of life, systems, and various fields. In the field of education itself, of course, must follow the current developments in order to be effective because a child is born for his time and an education regulator must be able to adapt to the times. All of that of course must be accompanied by a careful planning so that in the future it can run effectively and efficiently. It is necessary to formulate a national policy strategy through awareness and maturity of thought. In addition, public education needs to be adapted to meet the needs of expertise in the industrial era 4.0. Educators, education staff, managers of Islamic educational institutions also need new management and have a hand in filling industry 4.0. President Joko Widodo called for the time and energy of madrasa principals and teachers not to be wasted on making accountability reports, but could focus more on developing the quality of learning. Therefore, in Indonesia, it is necessary to start managing education in new ways, such as the use of e-RKAM.